Improvement of Biology Learning Results Through the Application of Problem-Based Instruction Approach Oriented Think Pair Share Learning Model - Fandi Ahmad; Nur Indah Sari (Yayasan Ahmar Cendekia Indonesia, 2019)
This research is a Classroom Action Research with the application of Problem Based Instruction approach oriented Think Think Share learning models in the learning process. The subjects of this study were 40th-grade students of SMP Negeri 40 Makassar in the first semester of the 2018/2019 school year. The implementation of this research consisted of two cycles. The data collected was analyzed descriptively. Based on the results of the study note that in the first cycle has not reached the expected standard classical limitations, this can be seen from the final value which only reached an average of 61.50 with a percentage of completeness of 65%. While in the second cycle the final grades of students have increased. This can be seen with the increase in the average value of student learning outcomes which reached 73.50 with a percentage of completeness of 80%. Based on the results it can be concluded that the application of the Problem Based Instruction approach oriented to Think Pair Share learning models can improve learning outcomes in biology subjects in the eighth grade at SMP Negeri 40 Makassar